Diretrizes para elaboração de documento de requisitos com ênfase nos requisitos funcionais - Kawai, Karina Kiyomi (Universidade Federal de São Carlos, 2005)
This work presents Guidelines to elaborate the Requirements Document (RD) based on Functional Requirements made up of three items: i) a Template to specify the Functional Requirements, which determines a set of basic information that should compose the requirement description; ii) Writing Recommendations that offer suggestions to avoid certain defects during requirement writing and iii) a Pre-Inspection Checklist that supports a brief evaluation of the requirements to help in deciding if the RD should be submitted to an inspection. Definition of such Guidelines were based on the analysis of some requirement specification standards, some writing recommendations suggested by some authors and mainly, on the evaluation of applying PBR-User, Checklist and TUCCA (Technique for Use Case Construction and construction-based requirements Analysis) inspection techniques in three different RDs. The main objective to define these Guidelines was to facilitate the application of TUCCA, which supports the elaboration of Use Case Model (UCM) and the inspection of RD, for which a tool that has the RD as input is being developed. The case study to evaluate the proposed Guidelines consisted of the application of PBR-User, Checklist and TUCCA in three RDs and posterior application of the three techniques in these same RDs after they were modified according to the proposed Guidelines. The obtained results showed that TUCCA application was made easier when RD followed the Guidelines and there was a defect reduction in RD thus increasing the quality of this document.
Keywords: Engenharia de software; Engenharia de requisitos; Técnicas de inspeção; Inspeção de documento de requisitos; Requisitos funcionais; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::ENGENHARIA DE SOFTWARE